Towards validating new enzymatic routes for synthetic conversion: 7, 10‐bis‐O‐(2, 2, 2‐trichloroethoxycarbonyl)‐10‐deacetyl baccatin III–ethyl acetate–water (1/1/1). Issue 3 (13th February 2015) - Wang, Li; Li, Ya‐jun; Li, Zheng‐wei
<x xml:space="preserve">Abstract</x> The title compound, C34H38Cl6O14·C4H8O2·H2O, prepared by the reaction of 10‐deacetyl baccatin III with 2, 2, 2‐trichloroethyl chloroformate in pyridine, crystallizes via strong intermolecular hydrogen bonds and noncovalent interactions between 7, 10‐bis‐O‐(2, 2, 2‐trichloroethoxycarbonyl)‐10‐deacetyl baccatin III (7, 10‐di‐Troc‐DAB), water and ethyl acetate. A detailed comparison of the molecular conformation with those of related structures is presented.